Expression of RPRM/rprm in the Olfactory System of Embryonic Zebrafish (Danio rerio) - Stanic, Karen; Quiroz, Alonso; Lemus, Carmen G.; Wichmann, Ignacio A.; Corvalán, Alejandro H.; Owen, Gareth I.; Opazo, Juan C.; Concha, Miguel L.; Amigo, Julio D. (Frontiers in Neuroanatomy, 2018)
The Reprimo (RPRM) family is composed of highly conserved single-exon genes. The expression pattern of this gene family has been recently described during zebrafish (Danio rerio) embryogenesis, and primarily locates to the nervous system. Its most characterized member, RPRM, which duplicated to give rprma and rprmb in the fish lineage, is known to act as a tumor-suppressor gene in mammalian models. Here, we describe in detail the spatiotemporal expression of three rprm genes (rprma, rprmb and rprml) within distinct anatomical structures in the developing peripheral and central nervous system. In the zebrafish, rprma mRNA is expressed in the olfactory placodes (OP) and olfactory epithelium (OE), rprmb is observed in the tectum opticum (TeO) and rprml is found in the telencephalon. At the protein level, Rprm (Rprma/Rprmb) is present in a subset of cells in the OP, and neurons in the OE, TeO, midbrain and hindbrain. Most importantly, the expression of RPRM has been conserved between teleosts and mammals evolution. Thus, we provide a reference dataset describing the expression patterns of RPRM gene products during zebrafish and mouse development as a first step to approach the physiological role of the RPRM gene family.